Malaysia@50 economic development, distribution, disparities - Jomo K. S.
Malaysia has grown and changed a great deal since it was formed on 16 September 1963. It was then seen as an unlikely nation hastily put together as a federation of British controlled territories in the region. Brunei's refusal to join at the eleventh hour and Singapore's secession before its second birthday only seemed to confirm such doubts.Yet, it has not only survived, but even thrived, often cited as a developing country worthy of emulation. Although constitutionally a federation, Malaysia has been more centralized than most federal states.The way forward requires greater sensitivity to the complex political economy of Malaysia's unlikely, but nonetheless resilient federation and ruling coalition.This book is published and distributed worldwide by World Scientific Publishing Co Pte Ltd except Malaysia.